PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENIPUAN DALAM JUAL BELI TAMBAK UDANG - Ais Wahyunita; Melisa Safitri (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
Criminal fraud is a form of crime against human wealth, such as criminal fraud in the sale and purchase of shrimp farming conducted by Wagiono and it had been decided by the Judicial Panel of District Court of Menggala Number 449/Pid.B/2019/PN.Mgl. The result of the study reveals that criminal liability against perpetrators of criminal fraud in the sale and purchase of shrimp farming based on The Decision No. 449/ Pid.B/2019 / PN.Mgl was found guilty or violates the provisions of Article 378 of the Criminal Code and sentenced to imprisonment for 1 (one) year while the judge's consideration in deciding the perpetrators was based on Decision Number 449/Pid.B/2019/PN.Mgl and the evidence, witness testimony, expert testimony, indictments and demands of the Public Prosecutor, the elements fulfilled in the Prosecutor's Indictment, as well as aggravating and mitigating factors for the accused.